KEPENTINGAN INDONESIA DALAM KERJASAMA SAFETY AND AIRWORTHINESS JOINT WORKING GROUP (SAJWG) DENGAN AUSTRALIA TAHUN 2024 - Nadirah, Nadirah; Azizah, Shela Nurul (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The purpose of this research is to analyze how aviation safety cooperation between the Air Force (AU) and the Royal Australian Air Force (RAAF) through the development of the 2024 Safety and Airworthiness Joint Working Group (SAJWG) program can anticipate and minimize the level of work accidents in the aviation environment so as to create a safe, efficient and professional aviation environment by adopting international aviation safety standards. This research uses qualitative data collection techniques through literature study and interviews with relevant agencies. The results showed that aviation safety cooperation through the SAJWG program was able to create a competent work environment. In addition, this aviation safety cooperation can enhance the bilateral cooperation that has been established between Indonesia and Australia.